Bone Mineral Densities in Individuals with Gilbert’s Syndrome: A Cross-Sectional, Case-Control Pilot Study - GY Minuk; R Greenberg; J Uhanova; K Hawkins; WD Leslie (Canadian Journal of Gastroenterology)
BACKGROUND: Unconjugated bilirubin inhibits osteoblastic proliferative activity in vitro, raising the possibility that Gilbert’s syndrome (GS) patients are at increased risk of osteoporosis.